The Benefits of Effective Teaching Style for HUMSS Students at Liceo De Pulilan Colleges: A Quantitative Study - Jesus, Dennis A. De (NPRC Journal of Multidisciplinary Research, 2024)
The present study investigates the benefits of different teaching styles to HUMSS students of Liceo De Pulilan Colleges. Teaching style is important because teachers play a big role in shaping the students' learning and behavior. That is why it needs to be suited to students especially because HUMSS students are facing professionals in the future. This research used quantitative research design in which the data was collected using survey questionnaires and analyzed using descriptive statistics. The results revealed that teaching style influences the student’s comfort, enjoyment, motivation, and inspiration. Most of the stakeholders say that teaching style has an overall impact on their engagement, confidence, and performance to study hard. It also affects how the student interacts with the teacher and classmates because when the teaching style is effective in the class, students are more active and have the willingness to participate which is why they can form a good bond and connection.